Model Perencanaan Pembangunan Desa di Wilayah Perbatasan antara Republik Indonesia dan Republik Demokratik Timor-Leste - Handrianus Vianey Melin Wula; Fransiskus Atok; Detson Ray Halomoan Sitorus (Society, 2024)
Villages are integral to national development and serve as a cornerstone for broader regional advancement. This study introduces an innovative village development planning model designed specifically for border areas, emphasizing the alignment of national policies with the needs of local communities. Using a qualitative descriptive approach, the research examines the distinctive challenges and opportunities faced by villages in border regions, with a particular focus on Napan Village, situated along the border between the Republic of Indonesia and the Democratic Republic of Timor-Leste. Data were collected through observation, semi-structured interviews, and document analysis and subsequently processed using a systematic framework of data reduction, presentation, and conclusion drawing. The proposed model highlights the importance of participatory planning and structured implementation to address community aspirations while ensuring alignment with national priorities. By offering a replicable framework for addressing the complexities of border areas, this study contributes to the discourse on governance and sustainable development, enhancing the capacity of border villages for inclusive and long-term growth.